Mobile Pulmonary Rehabilitation: Feasibility of Delivery by a Mobile Phone-Based Program - Whittaker, Robyn; Dobson, Rosie; Candy, Sarah; Tane, Taria; Burrowes, Kelly; Reeve, Julie; Tawhai, Merryn; Taylor, Denise; Robertson, Trina; Garrett, Jeffrey; Humphrey, Gayl; Brott, Tamzin; et al. (Frontiers in Computer Science, 2021)
Background: Pulmonary rehabilitation has been proven effective but is not well accessed due to transport, time, cost, and physical limitations of patients. We have developed a mobile phone-based PR program (mPR) that could be offered as an alternative for those unable to attend in-person. This was developed following formative research with patients, their families and clinicians. mPR has a core text message program plus an app that includes an action plan, exercise videos, lung visualisation, symptom score questionnaire and 1-minute sit-to-stand test. Methods: A 9-week non-randomized pilot study was conducted offering a prototype mPR program to 26 participants (and 4 family members). Results: Eight people (31%) opted for text messages only, and 18 (70%) chose text messages plus the mPR app. Three people stopped the program early, 20 said they would recommend it to others, 19 said it helped them to feel more supported, 17 said it helped them to change their behaviour. Conclusions: It is feasible to deliver PR support via mobile phones, including exercise prescription and support. Our mPR programme was appreciated by a small number of people with chronic respiratory disorders and family members. Suggestions for improvements are being used to inform the further development of our program. Registered with the Australia New Zealand Clinical Trials Registry ACTRN12619000884101p (www.anzctr.org.au).